Update on the Worsening Particle Radiation Environment Observed by CRaTER and Implications for Future Human Deep‐Space Exploration. Issue 3 (30th March 2018) - Schwadron, N. A.; Rahmanifard, F.; Wilson, J.; Jordan, A. P.; Spence, H. E.; Joyce, C. J.; Blake, J. B.; Case, A. W.; de Wet, W.; Farrell, W. M.; Kasper, J. C.; Looper, M. D.; et al.
Abstract: Over the last decade, the solar wind has exhibited low densities and magnetic field strengths, representing anomalous states that have never been observed during the space age. As discussed by Schwadron, Blake, et al. (2014, https://doi.org/10.1002/2014SW001084 ), the cycle 23–24 solar activity led to the longest solar minimum in more than 80 years and continued into the "mini" solar maximum of cycle 24. During this weak activity, we observed galactic cosmic ray fluxes that exceeded theERobserved small solar energetic particle events. Here we provide an update to the Schwadron, Blake, et al. (2014, https://doi.org/10.1002/2014SW001084 ) observations from the Cosmic Ray Telescope for the Effects of Radiation (CRaTER) on the Lunar Reconnaissance Orbiter. The Schwadron, Blake, et al. (2014, https://doi.org/10.1002/2014SW001084 ) study examined the evolution of the interplanetary magnetic field and utilized a previously published study by Goelzer et al. (2013, https://doi.org/10.1002/2013JA019404 ) projecting out the interplanetary magnetic field strength based on the evolution of sunspots as a proxy for the rate that the Sun releases coronal mass ejections. This led to a projection of dose rates from galactic cosmic rays on the lunar surface, which suggested a ∼20% increase of dose rates from one solar minimum to the next and indicated that the radiation environment in space may be a worsening factor important for consideration in future planning of human space exploration. We compare the predictions of Schwadron, Blake, et al. (2014, https://doi.org/10.1002/2014SW001084 ) with the actual dose rates observed by CRaTER in the last 4 years. The observed dose rates exceed the predictions by ∼10%, showing that the radiation environment is worsening more rapidly than previously estimated. Much of this increase is attributable to relatively low‐energy ions, which can be effectively shielded. Despite the continued paucity of solar activity, one of the hardest solar events in almost a decade occurred in September 2017 after more than a year of all‐clear periods. These particle radiation conditions present important issues that must be carefully studied and accounted for in the planning and design of future missions (to the Moon, Mars, asteroids, and beyond). Plain Language Summary: We examine the evolution of fluxes from galactic cosmic rays and recent solar energetic particle events to evaluate the recent evolution of radiation hazards in space and their implications for human and robotic exploration. Key Points: GCR radiation doses are rising faster than predicted previously SEP radiation events are large despite low solar activity Radiation environment is a significant factor for mission planning